Application of Jigsaw Learning Model to Increase Student Involvement in Civic Education - Rofiq Hafsi, Ainur (Journal of Islamic Elementary Education, 2023)
This study aims to evaluate the application of the Jigsaw learning model in enhancing student engagement in the Civics Education course. Using a quantitative approach with a quasi-experimental design, this study involved students enrolled in the course and measured their engagement before and after the implementation of the Jigsaw model through questionnaires, observations, and in-depth interviews. The results showed a significant increase in student engagement after the implementation of the Jigsaw model, reflected in active participation, learning motivation, and collaboration among students. This model proved effective in creating a more interactive and collaborative learning environment. However, some challenges such as students' readiness to collaborate were also identified. This study suggests that the Jigsaw model be applied more widely in other courses that require more active student engagement.